1993
DOI: 10.1017/s0308229600024983
|View full text |Cite
|
Sign up to set email alerts
|

Salivary losses of purine derivatives in sheep

Abstract: Developed models to estimate rumen microbial yield from the urinary excretion of purine derivatives fail to account for a complete absorbed purines (Chen et al., 1990a, Balcells et al., 1991). Ruminal degradation of purine derivatives recycled via saliva has been suggested as a possible explanation after detecting the presence of allantoin and uric acid in the sheep saliva (Chen et al. 1990b). However, it is not known to what extent these losses may be affected by dietary induced variations in saliva flow (Kay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…The results (Table 1) from the present study indicated that the transfer of allantoin-C to saliva and the rumen fluid was trivial (,1 %). These findings support those of Surra et al (1993Surra et al ( , 1997, and demonstrate that in sheep allantoin excretion via saliva is negligible, and therefore is unlikely to prejudice predictions of microbial yield from the rumen made using estimates of urinary allantoin excretion.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The results (Table 1) from the present study indicated that the transfer of allantoin-C to saliva and the rumen fluid was trivial (,1 %). These findings support those of Surra et al (1993Surra et al ( , 1997, and demonstrate that in sheep allantoin excretion via saliva is negligible, and therefore is unlikely to prejudice predictions of microbial yield from the rumen made using estimates of urinary allantoin excretion.…”
Section: Discussionsupporting
confidence: 76%
“…Incomplete urinary (renal) recoveries have also been reported following infusion of allantoin into the jugular vein of sheep (Chen et al 1991;Surra et al 1997) and for intravenously administered [ 15 N]uric acid in sheep (Chen et al 1998). Chen et al (1990a) suggested that saliva may be one significant non-renal route of excretion of PD, but other researchers (Surra et al 1993(Surra et al , 1997 have reported that the amounts transferred in saliva are negligible, thereby invoking the possibility of other non-renal routes of allantoin removal from the blood.…”
mentioning
confidence: 99%
“…However, Surra et al (1993) reported a lower concentration of PD in saliva of 8.5 μmol/L with a measured flow of saliva of 7 L/d. In further work, Surra et al (1997) estimated that the salivary secretion was only 0.003 of urinary PD excretion.…”
Section: Excretion Of Pd In Salivamentioning
confidence: 87%
“…Transfer of allantoin into the gut via saliva could be one route of non-renal loss of PD (Chen et al 1990b), but Surra et al (1993Surra et al ( , 1997 and Kahn & Nolan (2000) concluded that the fraction of the total loss of PD by this route was negligible. Kahn & Nolan (2000) also found only negligible amounts of radioactivity in saliva samples of sheep following the intra-jugular injection of labelled allantoin and calculated that less than 1 % of the radioactivity injected was transferred to the rumen via saliva.…”
mentioning
confidence: 99%